Strengthening the Governance of Village-Owned Enterprises Based on Local Potential to Realize Economic Independence in Asei Besar Village Jayapura Regency - Meinarni Asnawi; Pascalina Van Sweet Sesa; Hesti Selvianingrum; Karmel Kogoya; Ester Nofan Yumame; Khofifah Indah Lestari; Fernandino Gilbert Kalem Lemauk; Jali Dekiron Wanena; Nipis Tabuni; Nyait Yeklin Matuan (Inovasi Jurnal Pengabdian Masyarakat, 2026)
This Community Service Program (PKM) aimed to strengthen the governance of the Village-Owned Enterprise (Badan Usaha Milik Kampung/BUMKam) through a local potential-based empowerment approach to support the economic independence of Asei Besar Village, Jayapura Regency. The program addressed several governance challenges, including weak institutional capacity, the absence of standard operating procedures (SOPs), inadequate administrative and financial management, and the limited ability of managers to identify and develop local economic potential. The program employed a participatory approach consisting of education, training, interactive discussions, field observations, problem identification, and mentoring. The training covered institutional governance, organizational structure, administrative management, financial governance, accountability, transparency, and business planning based on local potential. The effectiveness of the program was evaluated using a pre-test and post-test involving 13 participants. Data were analyzed using the Shapiro–Wilk normality test followed by the Wilcoxon Signed Rank Test because the data did not meet the normality assumption. The results demonstrated a substantial improvement in participants' knowledge after the intervention. The average score increased from 47.77 in the pre-test to 82.54 in the post-test, representing an improvement of approximately 72.78%. The Wilcoxon Signed Rank Test indicated a statistically significant difference between pre-test and post-test scores (Z = -3.182; p = 0.001), confirming that the program effectively enhanced participants' understanding of institutional governance, organizational management, financial administration, business planning, transparency, accountability, and the utilization of local resources for sustainable BUMKam development. This program offers an integrated community empowerment model that combines institutional strengthening, participatory mentoring, governance improvement, financial management, and local potential mapping. The model contributes practical value for strengthening BUMKam governance and can serve as a replicable framework for promoting sustainable village economic development in indigenous and rural communities.